Inpatient versus outpatient rehabilitation for multiple sclerosis patients: effects on disability and quality of life. Issue 1 (December 2016) - Pappalardo, Angelo; D'Amico, Emanuele; Leone, Carmela; Messina, Silvia; Chisari, Clara; Rampello, L.; Torre, Lina; Patti, Francesco
Abstract Background The most suitable setting of rehabilitation for Persons with Multiple Sclerosis (PwMS) has not been identified so far because there is a general lacking of controlled studies. Aim of this study was to evaluate the treatment efficacy in terms of functional independence between two different settings. Methods A randomized, wait-list controlled study was performed at the MS Center of the University of Catania, and Rehabilitation Center of the Hospital of Acireale, Italy. Inclusion criteria were: a) range of age 18–75, b) Expanded Disability Status Scale ≥4.0 and ≤8.0 c) self-reported worsening of standing or walking abilities in the last 6 months. The examining physician was blind to patient allocation program. The Functional Independence Measure (FIM), and the 36-Health Survey Questionnaire (SF-36) data were collected at T0 (baseline) and T1 (follow-up). Results One-hundred forty-six patients were randomly assigned to three groups. Forty-nine PwMS were allocated in the outpatient treatment group (Group A), 49 patients in the inpatients treatment group (Group B) and 48 patients in the control waiting list (Group C). Both Group A and Group B showed a significant improvement in total FIM scores (p  = 0.03, p  = 0.008; respectively) at T1 compared to T0. No difference was found between Group A and B with regard to the FIM scores in the intergroup analysis. Group A showed significant improvement at T1 compared to T0 in all sub-items of SF-36 (p  < 0.05), contrary to Group B. A significant difference in total FIM score between the three groups was found (p  = 0.0003). The pairwise comparisons showed a significant difference between Group A vs Group C (p  = 0.003) and Group B versus Group C (p  = 0.001). Conclusions Inpatients and oupatients rehabilitation approaches both showed efficacy in improving total FIM score. Outpatient rehabilitation setting seems to be more effective in improving patients QoL.